Development of an In-House Rapid Antimicrobial Susceptibility Testing Protocol for Positive Blood Culture and Its Implementation in Routine Microbiology Laboratories - Cao, Min; Huang, Lin; Hu, Yanyan; Fang, Yinfei; Zhang, Rong; Chen, Gongxiang (Frontiers in Microbiology, 2021)
Bloodstream infections (BSI) are associated with high morbidity and mortality and remain a leading cause of death. Blood culture (BC) including the identification and the antimicrobial susceptibility testing of the causative microorganisms should be performed as soon as possible. In this study, we developed an in-house rapid antimicrobial susceptibility testing (rAST) protocol for positive BC. Firstly, the rAST was performed in the simulated positive BC of standard strains (Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923 and Pseudomonas aeruginosa ATCC 27853) at three different times to assess the reproducibility and operability by dispensing 4 drops of BC broth onto an MHA plate after a positive signal. Further, the rAST was performed in clinical positive BCs. The results of rAST at 4, 6, 8 and 18h of incubation were compared with results of the standard 16-20h disk diffusion method and the preliminary breakpoints of the rAST method were established according to the inhibition diameter of sensitive strains and resistant strains. Finally, the rAST was performed in the simulated positive BC of clinical strains to evaluate the availability of the preliminary breakpoints. The rAST results of standard strains were distributed evenly at three different times. Among the 202 clinical strains used to establish the preliminary breakpoints, the number of zone diameters that could be read and interpreted (60%, 87% 98% and 100%) increased with incubation time (4, 6, 8 and 18h), and the categorical agreement was acceptable, with total error rates of 3.0%, 2.3%, 2.1%, 1.3% at 4, 6, 8 and 18h of incubation, respectively. In conclusion, the in-house rAST protocol for positive BC can be implemented in routine laboratories. It provides reliable antimicrobial susceptibility testing results for bloodstream infection pathogens after 4-6h incubation.